Lifelong TMAO exposure exerts hypotensive effects in aged spontaneously hypertensive rats - Kopacz, Wojciech; Jaworska, Kinga; Koper, Mateusz; Ufnal, Marcin (Frontiers in Cardiovascular Medicine, 2025)
Trimethylamine N-oxide (TMAO), a bacterial metabolite associated with cardiovascular risk, has a debated role, with evidence suggesting both harmful and protective effects. We hypothesized that chronic TMAO supplementation modulates hypertension-related complications through alterations in the tissue renin-angiotensin system (RAS). Ten-week-old male spontaneously hypertensive rats (SHRs) were divided into two groups, receiving either water or TMAO-supplemented water for 80 weeks. Circulatory parameters, including hemodynamics, echocardiographic measurements, and pathomorphological assessments, tissue RAS expression and biomarker profiles, were evaluated. Rats treated with TMAO exhibited significantly higher plasma TMAO levels accompanied by significantly lower mean and systolic blood pressure and NT-proBNP levels. In the TMAO group, diuresis and natriuresis were numerically increased, and the left atrial size was smaller. No pathological effects of TMAO on the circulatory system were observed in rats. Echocardiographic parameters and age-related histopathological changes, including fibrosis in the heart and kidneys, were comparable between groups. TMAO-treated rats showed upregulated expression of RAS components, including angiotensinogen and AT1b and AT2 receptors, in the heart, kidneys, and colon. TMAO supplementation also increased blood and urinary levels of trimethylamine, a toxic precursor and metabolite of TMAO. In conclusion, lifelong exposure to TMAO improves circulatory function in hypertension, as evidenced by reduced blood pressure, lower NT-proBNP levels, and decreased left atrial size—findings consistent with a reduction in cardiac workload. The upregulation of RAS components may represent a compensatory response to the blood pressure-lowering effect of TMAO. However, the concurrent rise in potentially toxic TMA levels warrants further investigation to fully assess the long-term safety of TMAO supplementation.